2020
DOI: 10.30819/5123
|View full text |Cite
|
Sign up to set email alerts
|

Quantenoptik an Schulen. Studie im Mixed-Methods Design zur Evaluation des Erlanger Unterrichtskonzepts zur Quantenoptik

Abstract: Fostering students' conceptions about the quantum world -results of an interview study. In: Progress in Science Education (eingreicht) 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
(136 reference statements)
3
5
0
Order By: Relevance
“…The total normalized gain at 0.40 ± 0.21 is satisfactory and comparable to similar research projects (cf. 0.35 ± 0.21 in [34] (p. 156) or 0.37 ± 0.18 in [33] (p. 68)). The smallest learning gain was approximately 6% as indicated by the boxplot of g total in Figure 3, thus a non-negative impact can be recorded for all participants.…”
Section: Discussion Of Rq1mentioning
confidence: 96%
See 1 more Smart Citation
“…The total normalized gain at 0.40 ± 0.21 is satisfactory and comparable to similar research projects (cf. 0.35 ± 0.21 in [34] (p. 156) or 0.37 ± 0.18 in [33] (p. 68)). The smallest learning gain was approximately 6% as indicated by the boxplot of g total in Figure 3, thus a non-negative impact can be recorded for all participants.…”
Section: Discussion Of Rq1mentioning
confidence: 96%
“…Lastly, in this article, we understand adequate conceptual understanding to be achieved by students who scored at least 50% of the total post-test score as has been achieved in prior research (cf. [34]). In this regard, it is important to note that for the clarification of the first part of RQ1 the pretest score is not relevant.…”
Section: Instrumentsmentioning
confidence: 99%
“…An exploratory interview study identifying N = 25 students' difficulties regarding different quantum optics content domains is reported in Ref. [55]. In [55], it was shown that (a) students are predominantly unprejudiced towards the experimental and technical foundations of quantum optics experiments, e.g., with regard to the preparation of single-photon states in experiments with heralded photons via coincident events on binary detectors, and that (b) most of the students can cope with the underlying principles [55].…”
Section: Students' Conceptions On Quantum Optics Aspectsmentioning
confidence: 99%
“…[55]. In [55], it was shown that (a) students are predominantly unprejudiced towards the experimental and technical foundations of quantum optics experiments, e.g., with regard to the preparation of single-photon states in experiments with heralded photons via coincident events on binary detectors, and that (b) most of the students can cope with the underlying principles [55]. These indications are also supported in further studies, e.g., exploiting the technique of probing acceptance [51].…”
Section: Students' Conceptions On Quantum Optics Aspectsmentioning
confidence: 99%
See 1 more Smart Citation